"คติชนสร้างสรรค์" จากความเชื่อเรื่องครูหมอโนราที่ตำบลท่าแค จังหวัดพัทลุง - ณัฐวัตร อินทร์ภักดี (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This thesis aims to collect various forms of "creative folklore" derived from Khru Mo Nora belief in Tambon Takae, Changwat Phatthalung, and to analyze factors and functions of such creation. The data is collected from 2 types of Nora, ritual and entertaining, in the fieldwork during 2014-2017. The result shows that "creative folklore" derived from Khru Mo Nora belief in Tambon Takae, Changwat Phatthalung, appears in both ritual Nora and entertaining Nora. In ritual Nora, creations in the form of "creative folklore" are ritual and elements of ritual, which are newly created but aim to transmit the old beliefs from their way of life. There are also creations in the form of "cultural product" for sale, such as sacred relics and souvenirs derived from ritual and performing elements. In entertaining Nora, a troupe called "Khun Sri Sattha" is formed to perform Nora creatively–i.e., participating in "Khon Thai Khan Thep" show, performing a musical "Kraithong," and starring in a film "Serd." The troupe also creates new costumes for performing Nora in the manner of popular folk music. "Creative folklore" phenomena in Tambon Takae is caused by several factors. The first factor is the policy from administrative agencies inside and outside the community. The inside agencies are the municipality of Tambon Takae and Ban Takae school (Wan Khru 2500). The outside agencies is Phatthalung province and its cultural department. Another factor is the change of the ritual master in Nora Rong Khru Takae. The last but crucial factor is touristic context. This research reveals the ways of thinking in terms of creative folklore. The ways of thinking in ritual Nora are the emphasis on authenticity, creating a new ritual based on the belief of the old ritual, expanding the belief of Khru Mo Nora to the general audience, and adding to Nora Rong Khru ritual the aspect of cultural commodification. In case of entertaining Nora, the way of thinking in terms of creative folklore are creating a network of Ratcha Khru Nora into the "Thep Sattha" group, presenting Nora in modern media and other performances, and using the traditional Nora as base for a new creation. "Creative folklore" based on these ways of thinking has a function in transmitting the belief of Khru Mo Nora in both sacred world and profane world. It also has a function in sustaining the belief that Takae is the origin of Nora through ritual and icons which represent a unique identity of this space evidently. Hence, this study helps to understand the ways of thinking, dynamics, factors, and functions of "creative folklore" derived from Khru Mo Nora belief in Tambon Takae, Changwat Phatthalung, in contemporary Thai society. It could provide a way to study a various forms of creation from folklore as "creative folklore" in the frame of folkloristic study, and a way to study cultural commodification in other places.